A randomised controlled trial of treatments of childhood anxiety disorder in the context of maternal anxiety disorder: clinical and cost‐effectiveness outcomes. (31st July 2019) - Creswell, Cathy; Violato, Mara; Cruddace, Susan; Gerry, Stephen; Murray, Lynne; Shafran, Roz; Stein, Alan; Willetts, Lucy; McIntosh, Emma; Cooper, Peter J.
Abstract : Background: This study evaluated whether clinical and economic outcomes from CBT for child anxiety disorders in the context of maternal anxiety disorders are improved by adding treatment focused on (a) maternal anxiety disorders or (b) mother–child interactions. Methods: Two hundred and eleven children (7–12 years, 85% White British, 52% female) with a primary anxiety disorder, whose mothers also had a current anxiety disorder, were randomised to receive (a) child‐focused CBT with nonspecific control interventions (CCBT+Con), (b) CCBT with CBT for the maternal anxiety disorder (CCBT+MCBT), or (c) CCBT with an intervention targeting the mother–child interaction (CCBT+MCI). A cost‐utility analysis from a societal perspective was conducted using mother/child combined quality‐adjusted life years (QALYs). [Trial registration: https://doi.org/10.1186/isrctn19762288 ]. Results: MCBT was associated with immediate reductions in maternal anxiety compared to the nonspecific control; however, after children had also received CCBT, maternal outcomes in the CCBT+MCI and CCBT+Con arms improved and CCBT+MCBT was no longer superior. Neither CCBT+MCBT nor CCBT+MCI conferred a benefit over CCBT+Con in terms of child anxiety disorder diagnoses post‐treatment [primary outcome] ( adj RR : 1.22 (95% CI: 0.88, 1.67), p = .23; adj RR : 1.21 (95% CI: 0.88, 1.65), p = .24, respectively) or global improvement ratings ( adj RR : 1.25 (95% CI: 0.99, 1.57), p = .06; adj RR : 1.18 (95% CI: 0.93, 1.50), p = .17) or six and 12 months later. No significant differences between the groups were found on the main economic outcome measures (child/mother combined QALY mean difference: CCBT+MCBT vs. CCBT+Con: −0.04 (95% CI: −0.12, 0.04), p = .29; CCBT+MCI vs. CCBT+Con: 0.02 (95% CI: −0.05, −0.09), p = .54). CCBT+MCI was associated with nonsignificantly higher costs than CCBT (mean difference: £154 (95% CI: −£1, 239, £1, 547), p = .83) but, when taking into account sampling uncertainty, it may be cost‐effective compared with CCBT alone. Conclusions: Good outcomes were achieved for children and their mothers across treatment arms. There was no evidence of significant clinical benefit from supplementing CCBT with either CBT for the maternal anxiety disorder or treatment focussed on mother–child interactions, but the addition of MCI (and not MCBT) may be cost‐effective.